RACIAL DISCRIMINATION TOWARDS THE HAZARAS AS REFLECTED IN KHALED HOSSEINI’S THE KITE RUNNER - Handayani, Fadlilah Satya (LANTERN (Journal on English Language, Culture and Literature), 2016)
Khaled Hosseini’s novel entitled The Kite Runner is an American bestseller novel that represents racial conflict between the Pashtuns and Hazaras, two different races and ethnics in Afghanistan. The aims of this study are to find out the causes of racial discrimination, to analyze examples of racial discrimination, and to analyze the impacts of racial discrimination as depicted in The Kite Runner. Sociological approach and theories on racism and racial discrimination are used in this study. The result of this study shows that racial discrimination in The Kite Runner is caused by social structural factors and social psychological factors. Pashtuns and Hazaras differ in terms of religious beliefs, cultural practices, social status, and physical appearances. Pashtun as the majority race and ethnic in Afghanistan is Sunni Moslem while Hazara is Shi’a. Other reason why the Hazaras have been discriminated by Pashtun is their appearance that look like Chinese people. The Hazaras are also seen as the weakest and poorest race in Afghanistan, so that they are easily subjected to be killed, insulted, and tortured by Pashtuns. Moreover, racial discrimination in The Kite Runner causes some bad impacts to psychological health as well as to society. In The Kite Runner, it not only causes some bad impacts to Hassan’s psychological health but also causes a plan to commit the genocide, slavery, and oppression act toward the Hazaras. Therefore, it can be concluded that racial discrimination is harmful to the people and society because it teaches people to make judgments about others in terms of group-based expectations or standards.